Adsorption of Copper(II) Ion by Palm Oil Sludge Biochar Prepared by Pyrolysis: Equilibrium and Kinetics Studies - Leong, Wai Lun (2016)
Annually, million tons of Palm Oil Sludge (POS) were produced from palm oil mill industries as side-product. Thus, it is very crucial to utilize POS for more advantageous purposes, especially in the circumstances of low-cost adsorbent development. Throughout this study, POS has been utilized for the production of bio-char through conventional pyrolysis method. Adsorption of copper(II) ion from aqueous solution was investigated using Palm Oil Sludge Bio-char (POSB). Batch adsorption studies were conducted by varying the adsorbent dosage, contact time, contact speed and initial pH of copper(II) ion solution. The optimized parameters obtained from these studies are: 0.04 g of adsorbent dosage, 240 minutes of contact time, 150 rpm of contact speed and pH of 6. In addition, it was found that adsorption equilibrium was well described by Langmuir isotherm rather than Freundlich isotherm with maximum adsorption capacity of 45.31 mg/g of copper(II) ion onto the POSB. Moreover, adsorption data was fitted into three kinetic models which are Pseudo-first-order, Pseudo-second-order and Intra-particle diffusion models. As a result, kinetics of copper(II) ion adsorption was found to be Pseudo-second-order as the rate determining step. Experimental results clearly indicated that POSB has a homogeneous surface and it uptakes copper(II) ion by monolayer chemisorption. POSB can be an effective adsorbent for copper(II) ion removal from aqueous heavy metal solution.